2006
DOI: 10.1152/japplphysiol.01389.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced abdominal muscle fatigue in healthy humans

Abstract: The abdominal muscles have been shown to fatigue in response to voluntary isocapnic hyperpnea using direct nerve stimulation techniques. We investigated whether the abdominal muscles fatigue in response to dynamic lower limb exercise using such techniques. Eleven male subjects [peak oxygen uptake (VO2 peak) = 50.0 +/- 1.9 (SE) ml.kg(-1).min(-1)] cycled at >90% VO2 peak to exhaustion (14.2 +/- 4.2 min). Abdominal muscle function was assessed before and up to 30 min after exercise by measuring the changes in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 51 publications
7
66
1
Order By: Relevance
“…This latter finding suggests not only that exercise intensity is important but also that exercise duration plays a role in diaphragm fatigue. More recent studies have reported postexercise declines of about 15-25% in the gastric pressure response to magnetic thoracic nerve stimulation at work rates eliciting Ͼ90% of V O 2max (127,133), indicating that whole body exercise can also induce abdominal muscle fatigue.…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…This latter finding suggests not only that exercise intensity is important but also that exercise duration plays a role in diaphragm fatigue. More recent studies have reported postexercise declines of about 15-25% in the gastric pressure response to magnetic thoracic nerve stimulation at work rates eliciting Ͼ90% of V O 2max (127,133), indicating that whole body exercise can also induce abdominal muscle fatigue.…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%
“…These techniques have also been used to show that whole body endurance exercise can induce fatigue of the diaphragm (11-14, 52, 72) and abdominal muscles (127,133). In fit normal subjects exercising to exhaustion (8 -10 min) at intensities that elicit at least 80 -85% of V O 2max , reductions of 15-30% in the transdiaphragmatic pressure response to supramaximal stimulation of the phrenic nerves were consistently obtained within 10 min after exercise, and transdiaphragmatic pressures did not return to near preexercise values until 1-2 h postexercise (11-14, 52, 72).…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…In the course of exhaustive high-intensity exercise (¸85% of maximal oxygen consumption), inspiratory muscles are known to fatigue (Johnson et al 1993;Mador et al 1993;Perret et al 1999Perret et al , 2000 but also, expiratory muscle fatigue (EMF) was recently shown to develop under similar conditions (Taylor et al 2006;Verges et al 2006b). Expiratory muscles may be even more prone to fatigue than inspiratory muscles as several studies have shown that expiratory muscles are in general less oxidative than S. Verges · Y. Sager · C. Erni · C. M. Spengler Institute of Physiology and Center for Integrative Human Physiology (ZIHP), University of Zurich, Zurich, Switzerland inspiratory muscles (Lieberman et al 1973;Uribe et al 1992) and are therefore expected to be less fatigue resistant.…”
Section: Introductionmentioning
confidence: 99%
“…Although volitional measures of fatigue may be confounded by the presence of central fatigue, the decrease in end-inspiratory V rc,p with no change in the other two compartments is considered an independent indicator of inspiratory rib cage muscle fatigue. Furthermore, the few studies assessing respiratory muscle fatigue after exercise with both measurement of oesophageal and gastric pressure during nerve stimulation and during voluntary respiratory manoeuvres show a decrease in twitch pressures with smaller decreases (or no significant change) in pressures during voluntary manoeuvres (Johnson et al, 1993;Mador et al, 1993;Taylor et al, 2006;Kabitz et al, 2008;Taylor and Romer 2008).…”
Section: Limitationsmentioning
confidence: 99%